Optimalisasi Penggunaan Media Sosial Instagram Oleh Diskominfo Provinsi Jambi Dalam Penyebaran Informasi Kepada Publik - Artha, Kania Chairunnisa Dwi; Santoso, Hudi (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
This research focuses on Content Optimization on Social Media Instagram of the Jambi Province Diskominfo. Social media is a forum for interaction that is done online / online, so that information is obtained through social media such as Instagram. The Jambi Province Diskominfo actively uses social media and uses Instagram to spread news/information in Jambi Province. This research aims to explain the Jambi Provincial Diskominfo optimizing the dissemination of public information through Instagram social media and explain the obstacles faced by the Jambi Provincial Diskominfo in disseminating information through Instagram social media. This study uses a qualitative approach. The results of the study show that the Jambi Provincial Diskominfo has used Instagram quite well in optimizing the dissemination of public information through features such as feeds, reels, and instastories. However, the entertainment aspect and social interaction have not been optimally optimized, causing low appeal, especially for young people. The main obstacles in content management include limited human resources, budget, low digital literacy of the community, and lack of audience participation.